RANCANG BANGUN SISTEM PENGELOLAAN DATA LIMBAH B3 MENGGUNAKAN METODE RAPID APPLICATION DEVELOPMENT - Corriny, Nety; Indah, Dwi Rosa (Program Studi Pendidikan Informatika, Universitas Citra Bangsa, 2023)
Currently, the development of science and information technology is increasingly affecting various fields of life significantly. PT Bukit Asam is a coal mining company. PT Bukit Asam Tbk. generates various wastes, both solid and liquid, during the coal mining process and office operations. This waste includes hazardous and toxic waste (B3) and non-B3 waste. A waste data management reporting application system is needed to support proper and accurate B3 waste management policies. B3 waste data reporting still uses Microsoft Excel, where the data input process can cause redundancy and data loss, therefore a computerized system that can store and process waste data is needed by applying the Rapid Application Development (RAD) method in system development which starts with the stages of requirement planning, system design, and implementation while this application is built using the AngularJS framework which is web-based. This development method was chosen because it has benefits that can produce a fast and high-quality system. The results of this study produce a system that can facilitate the management and recording of waste data using the MySQL database system.